Staphylococcus aureus PSM Peptides Modulate Human Monocyte-Derived Dendritic Cells to Prime Regulatory T Cells - Richardson, Jennifer R.; Armbruster, Nicole S.; Günter, Manina; Henes, Jörg; Autenrieth, Stella E. (Frontiers in Immunology, 2018)
Staphylococcus aureus (Sa), as one of the major human pathogens, has very effective strategies to subvert the human immune system. Virulence of the emerging community-associated methicillin-resistant Sa (CA-MRSA) depends on the secretion of phenol-soluble modulin (PSM) peptide toxins e.g. by binding to and modulation of innate immune cells. Previously, by using mouse bone marrow-derived dendritic cells we demonstrated that PSMs in combination with various Toll-like receptor (TLR) ligands induce a tolerogenic DC phenotype (tDC) characterized by the production of IL-10 and impaired secretion of pro-inflammatory cytokines. Consequently, PSM-induced tDCs favored priming of CD4+CD25+FoxP3+ Tregs with suppressor function while impairing the Th1 response. However, the relevance of these findings for the human system remained elusive. Here, we analyzed the impact of PSMα3 on the maturation, cytokine production, antigen uptake, and T cell stimulatory capacity of human monocyte-derived DCs (moDCs) treated simultaneously with either LPS (TLR4 ligand) or S. aureus cell lysate (TLR2 ligand). Herein, we demonstrate that PSMs indeed modulate human moDCs upon treatment with TLR2/4 ligands via multiple mechanisms, such as transient pore formation, impaired DC maturation, inhibited pro- and anti-inflammatory cytokine secretion, as well as reduced antigen uptake. As a result, the adaptive immune response was altered shown by an increased differentiation of naïve and even CD4+ T cells from patients with Th1/Th17-induced diseases (spondyloarthritis and rheumatoid arthritis) into CD4+CD127-CD25hiCD45RA-FoxP3hi regulatory T cells (Tregs). This Treg induction was mediated most likely by direct DC T-cell interaction in combination with indolamin-2,3-dioxygenase expression. Thus, PSMs from highly virulent Sa strains affect DC functions not only in the mouse, but also in the human system, thereby modulating the adaptive immune response and probably increasing the tolerance towards the bacteria. Moreover, PSMα3 might be a novel peptide for tolerogenic DC induction that may be used for DC vaccination strategies.